Compound 21, a selective agonist of angiotensin AT2 receptors, prevents endothelial inflammation and leukocyte adhesion in vitro and in vivo. (29th June 2015) - Sampson, Amanda K; Irvine, Jennifer C; Shihata, Waled A; Dragoljevic, Dragana; Lumsden, Natalie; Huet, Olivier; Barnes, Tyrone; Unger, Thomas; Steckelings, Ulrike M; Jennings, Garry L; Widdop, Robert E; Chin‐Dusting, Jaye P F
Abstract : Background and Purpose: Angiotensin AT2 receptors are upregulated in disease states such as atherosclerosis and blockade of the AT2 receptors exacerbates plaque formation. Direct stimulation of these receptors is anti‐atherogenic but the mechanisms and pathways involved remain unknown. We examined the effect of direct AT2 receptor stimulation with Compound 21 (C21) on the leukocyte adhesion cascade in vitro, right through to plaque formation in vivo . Experimental Approach: Effects of C21 on TNFα‐induced inflammation were assessed in human umbilical vein endothelial cells (HUVECs), activation of monocytes, polarisation of monocyte‐derived macrophages and in intact mouse aortae. Key Results: C21 attenuated TNFα‐induced: monocyte adhesion to cultured HUVECs, adhesion molecule expression and abolished TNFα‐induced ROS production. TNFα‐induced NFκB translocation from the cytoplasm to the nucleus, essential for cytokine production, was prevented by C21. C21 did not influence monocyte activation or macrophage polarisation but did reduce TNFα and IL‐6 mRNA expression in M1 macrophages. The anti‐inflammatory effects of C21 were abolished by an AT2 receptor antagonist confirming that the effects of C21 were AT2 receptor‐mediated. Also, leukocyte adhesion and cytokine gene expression, induced by high‐fat diet (HFD), was attenuated in ApoE ‐/‐ mice treated with C21. Plaque size and stability were improved with C21 treatment with increased smooth muscle cell composition and decreased lipid size, compared with HFD‐saline treated mice. Conclusion and Implications: C21 prevented TNFα‐induced and HFD‐induced vascular inflammation in vitro and in vivo . Our data provide strong evidence that the anti‐atherosclerotic actions of C21 were due to vascular anti‐inflammatory effects, mediated by AT2 receptors. Linked Articles: This article is part of a themed section on Inflammation: maladies, models, mechanisms and molecules. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2016.173.issue-4